2011
DOI: 10.2320/matertrans.m2011021
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Boundary Resistance Effect on Non-Equilibrium Energy Transport in Metal-Dielectric Thin Films Heated by Femtosecond Pulse Lasers

Abstract: The aim of this study is to investigate the effect of interfacial thermal boundary resistance (TBR) at a metal-dielectric interface on nonequilibrium energy transport in Au/SiO 2 films heated by femtosecond pulse lasers. In this paper we suggest a combined set of numerical models that include the two-temperature model (TTM) for a metal side and the heat conduction equation for a dielectric layer. In addition, the TBRs between metal and nonmetal layers are calculated using thermal conductance, which is closely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Consequently, hot electrons excited by the deposited laser energy can penetrate deep into the material before an interaction with the lattice takes place, which is why L c can noticeably exceed l α . As the energy transport across the metallic–dielectric interface can occur via electron–phonon and phonon–phonon coupling [ 35 , 36 ], the increased interfacial electron density resulting from the diffusion of the hot electrons leads to an increased interfacial energy transfer [ 24 , 28 ]. In contrast to the energy coupling to the uncoated glass surface, which is solely based on strongly non-linear multiphoton processes, this leads to a stronger, more uniform deposition of the energy to the fused silica substrate and thus to the significant reduction of the LIPSS formation threshold.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, hot electrons excited by the deposited laser energy can penetrate deep into the material before an interaction with the lattice takes place, which is why L c can noticeably exceed l α . As the energy transport across the metallic–dielectric interface can occur via electron–phonon and phonon–phonon coupling [ 35 , 36 ], the increased interfacial electron density resulting from the diffusion of the hot electrons leads to an increased interfacial energy transfer [ 24 , 28 ]. In contrast to the energy coupling to the uncoated glass surface, which is solely based on strongly non-linear multiphoton processes, this leads to a stronger, more uniform deposition of the energy to the fused silica substrate and thus to the significant reduction of the LIPSS formation threshold.…”
Section: Resultsmentioning
confidence: 99%
“…They demonstrated that that the temporal evolution of electron and phonon temperatures in nanometre sized gold films was very different from macro-scale films. The effect of thermal boundary resistance on nonequilibrium energy transport in metal-dielectric thin films because of femtosecond pulse laser heating was examined by Lee and Lee [13]. Their findings indicated that the thermal boundary resistance rapidly increased the thermal conductivity at the interface, and it became dominant at an early stage of laser irradiation over a very short period.…”
Section: Introductionmentioning
confidence: 98%
“…And at the same total fluence, the oscillation amplitudes in Au-plated ZnO are much larger. Electrons in Au film are heated to a high temperature during irradiation, and the fast hot-electron diffusion by the Au film increases the interfacial carrier density and enhances the interfacial electron-phonon coupling [24,25]. The higher interfacial carrier density in the Au-plated ZnO can lead to a shorter oscillation period of ablation areas.…”
mentioning
confidence: 98%